RADIO MARKETING COMMUNICATION STRATEGIES IN AN EFFORT TO INCREASE THE NUMBER OF LISTENERS IN THE INDUSTRY 4.0 ERA IN 2021 ( Study on Radio El John 89.7 FM Baturaja ) - Sasora, Fajar; toreza, Rahmad fajrido; suryani, Eny inti (Journal of Public Relations and Digital Communication (JPRDC), 2024)
Radio as one of the audio mass media , radio ever has become a superior event whose strength is really taken into account . along with development technology communication radio start state dimmed and replaced by audio visual media, however until moment it's still radio still exists and airs one of them namely Radio El John 89.7 FM Baturaja . This radio has a superior program namely tourism, business, investment. Study This use approach qualitative descriptive For describe communication strategies marketing El John Radio 89.7 FM through featured programs in effort maintain radio listeners. Results study show that this radio use communication strategies marketing used with more utilise social media channels in effort reach listener from circles millennials and their results significant ie happen enhancement listener to radio's flagship programs